Problem-Based Learning Model to Increase Self-Efficacy of Grade IV Elementary School Students - Ponsa, Angela Carolina; Wati, Tri Linggo (Universitas Cokroaminoto Palopo, 2025)
This study aims to determine the effect of the Problem-Based Learning (PBL) model on improving the self-efficacy of fourth-grade elementary school students in science subjects. The research was conducted at SDN Ngampelsari, Sidoarjo Regency, East Java, Indonesia, involving 32 fourth-grade students. Self-efficacy refers to students’ belief in their ability to face challenges, complete tasks, and achieve learning goals. It plays a critical role in enhancing motivation, learning behavior, and academic success. This study employed a quantitative method with a pre-experimental design, using a one-group pretest-posttest format. The instrument used was a self-efficacy questionnaire distributed before and after the implementation of the PBL model. The model was applied through structured learning activities involving real-life problem solving, collaboration in group work, and the development of critical thinking skills to find solutions. The contextually meaningful tasks helped students actively engage with the material and with one another. The data collected were analyzed using the Wilcoxon Signed Rank Test and N-Gain analysis. The Wilcoxon test showed a significance value of 0.000, which indicates a statistically significant difference in students' self-efficacy before and after treatment. The average N-Gain score was 0.7835, categorized as high. These findings demonstrate that the PBL model had a strong positive effect on students' psychological readiness for learning by enhancing their confidence, active participation, and persistence when facing challenges. In conclusion, the Problem-Based Learning model is not only effective for improving cognitive outcomes but also contributes to the development of students’ non-cognitive competencies. It is recommended for wider implementation in elementary schools to promote meaningful, student-centered, and empowering learning environments aligned with 21st-century education goalsy.